Газификация углей в жидком высокотемпературном теплоносителе с получением синтез-газа - Гликин, М. А.; Гликина, И. М.; Зубцов, Е. И. (НТУ "ХПИ", 2006)
Розглянуто проблеми сучасної енергетики та показано можливість переробки вугілля у синтез-газ з використанням технології газифікації у рідкому високотемпературному теплоносії (РВТ). Наведено принципову схему лабораторної установки для проведення даного процесу та отримані експериментальні дані. Розраховано ступінь перетворення вугілля в залежності від часу проведення процесу. Запропоновано схему промислового реактора газифікації вугілля у РВТ.

Problems of modern power are considered and the opportunity of processing of coal in synthesis-gas with use of gasification technology in the liquid high-temperature heat-carrier (LHTHC) is shown. The basic scheme of laboratory installation for carrying out of the given process and the received experimental data is presented. The degree of transformation of coal depending on time of course of process is calculated. The scheme of an industrial reactor of gasification of coal in LHTHC is offered.
Keywords: паровая конверсия; антрацит; реактор-газификатор; барботажные аппараты